2020
DOI: 10.5897/jvmah2019.0779
|View full text |Cite
|
Sign up to set email alerts
|

Causes of organ condemnations in cattle at slaughter and associated financial losses in Siaya County, Kenya

Abstract: Cattle production is an important economic activity worldwide. Its potential, however, is not fully maximized owing to disease conditions, some causing condemnation and wastage of edible organs at slaughter and a threat of zoonoses. This work aimed at establishing definitive causes of organ condemnation and financial losses in cattle from three slaughterhouses (Kaumara, Siaya, and Ugunja) in Siaya County, Kenya, through a cross-sectional study. Out of 112 cattle slaughtered, 75 (67%) had one or more organs con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The latter observed that carcasses were processed on bare ground, meats were washed with water from the gutters and effluents channelled to nearby natural water bodies, which may be sources of drinking water for the communities around the abattoirs [11,72,96,97]. Outside Nigeria, poor sanitary conditions of SHs and condemnation of meats due to various disease conditions have be reported in South Africa [98,99], Ethiopia [100], Iran [101], Tanzania [102], Namibia [103] and Kenya [104].…”
Section: Table 5 Association Between Geographical Location Of Slaught...mentioning
confidence: 99%
“…The latter observed that carcasses were processed on bare ground, meats were washed with water from the gutters and effluents channelled to nearby natural water bodies, which may be sources of drinking water for the communities around the abattoirs [11,72,96,97]. Outside Nigeria, poor sanitary conditions of SHs and condemnation of meats due to various disease conditions have be reported in South Africa [98,99], Ethiopia [100], Iran [101], Tanzania [102], Namibia [103] and Kenya [104].…”
Section: Table 5 Association Between Geographical Location Of Slaught...mentioning
confidence: 99%